Combustion synthesis of α-Si3N4 with the addition of NH4Cl. Issue 16 (November 2018) - Tian, Zhaobo; Zhang, Jie; Sun, Siyuan; Cui, Wei; Zou, Yifeng; Cheng, Huiming; Liu, Guanghua
Abstract: This paper reports combustion synthesis of α-Si3 N4 with the addition of NH4 Cl. The effect of NH4 Cl on the phase composition of the products is investigated, and the reaction mechanism in the nitridation of Si with the participation of NH4 Cl is discussed. The content of α-Si3 N4 in the products increases with increasing content of NH4 Cl in the starting compositions, and reaches 93% when 10 wt% NH4 Cl is added. It is proposed that the addition of NH4 Cl promotes the nitridation of Si by gaseous reaction and improves the formation of α-Si3 N4 . In the reaction, NH4 Cl decomposes into HCl and NH3, and HCl reacts with Si to form SiCl4, which is later nitridized into Si3 N4 . In the nitridation of Si, HCl acts as a catalyst and a carrier to transfer Si atoms from solid and liquid Si particles into gas phase. The contribution of NH3 to the nitridation of Si is limited, and most N atoms required for the synthesis of Si3 N4 are provided by N2 .